Survival of an elderly patient with limited cutaneous systemic sclerosis, pretamponade and pulmonary hypertension. (April 2013) - Naboush, Ali; Abdallah, Mokhtar; Asti, Deepak; Goldstein, Mark
Objective: Conservative management of systemic sclerosis-induced pretamponade in the setting of pulmonary hypertension.Methods: A case report with a review of the literature.Results: An 81-year-old Caucasian woman with a history of limited cutaneous systemic sclerosis was admitted to the hospital for mechanical fall and shortness of breath. In the emergency department, she was cyanotic, in severe respiratory distress, tachycardic and hypertensive with oxygen desaturation. A chest x-ray showed cardiomegaly with bilateral infiltrates. An echocardiogram showed large pericardial effusion compressing mainly on the left ventricle, and right atrial collapse at the end of the diastole, with peak pulmonary pressure of 65 mmHg. The patient was managed conservatively with labetelol, intravenous fluids and furosemide until hemodynamically stabilized. The next day she had an elective pericardiotomy with a window. A total of 700 ml of serous exudative fluid was removed. Following the pericardial fluid drainage, the patient's symptoms resolved and a repeat echocardiogram showed no pericardial effusion and better left ventricular filling. The patient continued to be asymptomatic after 6 months of follow-up.Conclusion: Conservative management of systemic sclerosis-induced pretamponade is effective and may be superior to emergent pericardiocentesis.